Zwitterionic polypeptides bearing carboxybetaine and sulfobetaine: synthesis, self-assembly, and their interactions with proteins. Issue 10 (26th February 2018) - Tsai, Yu-Lin; Tseng, Yu-Chao; Chen, Yan-Miao; Wen, Tain-Ching; Jan, Jeng-Shiung
Abstract : Zwitterionic polypeptides bearing carboxybetaine and sulfobetaine were synthesized and their self-assembly and protein interactions were evaluated. Abstract : We report the synthesis of zwitterionic homopolypeptides and block copolypeptides bearing carboxybetaine and sulfobetaine (CB and SB) via combining γ-propargyl-l -glutamate NCA polymerization with efficient Huisgen's click reaction. The zwitterionic homopolypeptides adopted versatile chain conformations upon varying the solution pH, depending on the chain length and functional group. The zwitterionic homopolypeptides with a degree of polymerization (DP) of 60 adopted stable α-helical conformation due to their elongated side-chain, whereas the short ones (DP = 20) adopted different conformations at varying solution pH. Their interactions with proteins depend on the chain conformation and zwitterionic group. The short one bearing SB exhibited very low interactions with lysozyme and myoglobin due to its coil and zwitterionic nature. A preliminary study showed that the zwitterionic block copolypeptides self-assemble to form vesicles with tunable molecular packing and solution behavior. These biodegradable/biocompatible, zwitterionic polypeptides may be promising materials in many applications such as non-fouling coatings and drug delivery.